IMPROVING STUDENTS' LEARNING MOTIVATION THROUGH LEARNING MODELSPROBLEM BASED LEARNING ADAPTIVE TECHNOLOGY BASED - Pauziah, Fadillah (CIVITAS (JURNAL PEMBELAJARAN DAN ILMU CIVIC), 2025)
Student learning motivation is the initial step in the learning process that determines the direction of learning outcomes. Low learning motivation is a habit of conventional and monotonous teaching contexts that do not stimulate student involvement. The purpose of this study is to analyze the effectiveness of the implementation of the learning model.Problem Based Learning(PBL) based on adaptive technology in improving learning motivation of students in Class X-2 of SMA Negeri 3 Rantau Utara. The study used the Classroom Action Research (CAR) approach with the Kemmis and McTaggart spiral model which was implemented in two action cycles including the planning stage, action implementation, observation, and reflection. The subjects of the study were students in class X-2 at SMA Negeri 3 Rantau Utara with a total of 36 students. Data collection instruments were through observation, questionnaires and interviews. Data were analyzed using quantitative descriptive methods. The results of the study showed that learning innovation through Problem Based Learning (PBL) based on adaptive technology had a major impact on significantly improving students' learning motivation, as evidenced byAttention, Relevance, Confidence, as well as Satisfaction The results of the learning motivation indicator components from Keller showed a consistent and significant increase in the average value of student motivation in (Pre-cycle) amounting to 60.2 and (Cycle 1) the average value was 72.1 and (Cycle 2) the average value was 88.6. ModelProblem Based Learning Adaptive technology-based learning is very relevant for use in 21st century learning, especially in building and improving student learning motivation.